2011
DOI: 10.1517/14728222.2011.560837
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ligand-operated chaperone sigma-1 receptors in the treatment of neuropsychiatric disorders

Abstract: Introduction Current conventional therapeutic drugs for the treatment of psychiatric or neurodegenerative disorders have certain limitations of use. Psychotherapeutic drugs such as typical and atypical antipsychotics, tricyclic antidepressants, and selective monoamine reuptake inhibitors, aim to normalize the hyper- or hypo-neurotransmission of monoaminergic systems. Despite their great contribution to the outcomes of psychiatric patients, these agents often exert severe side effects and require chronic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
190
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(195 citation statements)
references
References 134 publications
0
190
0
1
Order By: Relevance
“…The σ1 receptor has also been postulated to act as a molecular chaperone that regulates cellular survival and synaptogenesis (Hayashi and Su, 2007;Tsai et al, 2009;Fujimoto et al, 2012). Ligands selective for σ1 receptors have been reported to exert antidepressant-like, anxiolytic and analgesic actions in preclinical studies (Hayashi et al, 2011). In addition, σ1 receptor occupation has been linked to neurorestorative effects and has been suggested as a novel therapeutic target for the treatment of cognition deficit (Maurice et al, 1994;Urani et al, 1998;Maurice, 2002;Espallergues et al, 2007;Antonini et al, 2011;van Waarde et al, 2011;Kourrich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The σ1 receptor has also been postulated to act as a molecular chaperone that regulates cellular survival and synaptogenesis (Hayashi and Su, 2007;Tsai et al, 2009;Fujimoto et al, 2012). Ligands selective for σ1 receptors have been reported to exert antidepressant-like, anxiolytic and analgesic actions in preclinical studies (Hayashi et al, 2011). In addition, σ1 receptor occupation has been linked to neurorestorative effects and has been suggested as a novel therapeutic target for the treatment of cognition deficit (Maurice et al, 1994;Urani et al, 1998;Maurice, 2002;Espallergues et al, 2007;Antonini et al, 2011;van Waarde et al, 2011;Kourrich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…8 Specific activation of the Sig-1R thus affects multiple physiological pathways, and these mechanisms offer a rationale for the functional recovery and cognitive effects of Sig-1R agonists observed in models of central nervous system injury and functional impairment. 9 Cutamesine (1-(3,4-dimethoxyphenethyl)-4-(3-phenylpropyl) piperazine dihydrochloride, SA4503), 10 an orally available, central nervous system active, selective agonist of the Sig-1R, enhanced functional recovery after experimental stroke in rats when treatment commenced 48 hours after stroke and continued for 1 month, without affecting infarct size. 3 Treatment with cutamesine in vivo increased the levels of the synaptic proteins neurabin and neurexin in the peri-infarct area, whereas in vitro the compound stimulated neurite outgrowth in primary cortical neuronal cultures.…”
mentioning
confidence: 99%
“…Sigma-1R has been implicated in a large variety of cellular processes, such as cellular redox, neurotransmitter release, inflammation, cellular differentiation, neuronal survival and synaptogenesis. It seems to act as a molecular chaperone, though the characteristics of Sigma-1R interactions in each pathway are still unclear [126,127].…”
Section: Sigma-1 Receptormentioning
confidence: 99%
“…Activation of Sigma-1R was also shown to decrease expression levels of Bax and caspase 3, which are associated with ER stress-mediated apoptosis, and hence aids cell survival in cells affected by amyloid beta [129]. Sigma-1R activation also provides significant protection against oxidative damage by reducing ER stress [123,124,126,130]. It was recently suggested that through its interaction with Rac1-GTPase at the MAMs, Sigma1R induces mild oxidative stress, preventing apoptosis [131].…”
Section: Sigma-1 Receptormentioning
confidence: 99%